Sentiment News in the Nigerian Reit Market: Source and its Dynamic Nature - Fateye, Tosin Babatola; A. Ajayi, Cyril; B. Peiser , Richard (Journal of African Real Estate Research, 2024)
In this study, we assess the source and dynamic nature of sentiment news on the Nigerian REIT market. The study adopts direct survey method and the Nigerian stockbrokers were surveyed through close-end questionnaire instrument. The data collected were analysed by weighted mean score and stepwise regression model. The result showed that the prominent source of biased news in the property stock market is pronouncements/announcements on economic indices and capital markets. The REIT market is more active, with often buying decisions during the optimistic market mood driven by good news. The pessimism market condition is characterized by the decision to sell, often dominated by pessimistic investors; the optimistic investors take caution, leading to a dull market and low return on investment. Findings also revealed that sentiment news from pronouncements/announcements significantly explains the dynamic behaviour of investors during the optimistic market condition; the media/press report significantly explains investor behaviour towards property stock in the pessimism market condition. The study concluded that the need to examine irrational behaviour attributed to sentiment news is imperative to optimal investment decisions when thinking of investment in the REIT market.